2020
DOI: 10.3988/jcn.2020.16.3.438
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Risk Factors for a Poor Prognosis in Patients with Anti-N-Methyl-D-Aspartate Receptor Encephalitis and Construction of a Prognostic Composite Score

Abstract: Background and Purpose Anti- N -methyl-D-aspartate receptor (NMDAR) encephalitis is the most-common form of autoimmune encephalitis, but its early diagnosis is challenging. This study aimed to identify the risk factors for a poor prognosis in anti-NMDAR encephalitis and construct a prognostic composite score for obtaining earlier predictions of a poor prognosis. Methods We retrospectively analyzed the clinical data, laboratory indexes, imaging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
9
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 33 publications
4
9
1
Order By: Relevance
“…Little information about prognosis of late‐onset anti‐NMDARE in China has been available in recent years and were inconsistent 8,16 . Our conclusion is in line with several previous studies 7,9,17,18 . The possible reason might be that body immunity and function declined with age, so that older individuals were more vulnerable to various age‐related complications.…”
Section: Discussionsupporting
confidence: 83%
“…Little information about prognosis of late‐onset anti‐NMDARE in China has been available in recent years and were inconsistent 8,16 . Our conclusion is in line with several previous studies 7,9,17,18 . The possible reason might be that body immunity and function declined with age, so that older individuals were more vulnerable to various age‐related complications.…”
Section: Discussionsupporting
confidence: 83%
“…Previous studies of prognostic risk factors of AE reported similar findings (28). Mo et al revealed that age, disturbance of consciousness, and ≥ 50% slow waves on EEG were independent risk factors of a poor AE prognosis(29). In addition, the proportion of abnormal brain MRI signals in the poor-prognosis group was significantly higher than that of the good-prognosis group, which was consistent with prior studies.…”
supporting
confidence: 70%
“…In our study, we also found that the increasing age was significantly associated with a poorer long-term prognosis of patients with AE. This conclusion is in line with several previous studies ( 23 25 ). However, no association was found between age and short-term first-line treatment response in this study.…”
Section: Discussionsupporting
confidence: 94%